A differentiated account of the role of trust in consumers' acceptance of genetically modified foods in Germany. (19th May 2008) - Boecker, Andreas
This paper proposes a sequential model to contrast the causal chain and associationist models on the role of trust in GM food acceptance. Data from 60 laddering interviews suggest the role of trust in evaluating the perceived consequences of GM food production and consumption is small and that the link between risk and trust is rather weak, too. Lending further support to the relevancy of the proposed model, the data support the hypothesis that respondents who are likely to accept GM food raise trust issues significantly less often than respondents who are unlikely to accept GM food. The analysis further identifies the segment with intermediate acceptance likelihood as most important for the future uptake of the technology.